Numerical Simulation of Microwave Scattering from Sea Ice Based on The Finite Element Method - Xu, Xu; Doulgeris, Anthony Paul; Melandsø, Frank; Brekke, Camilla (2016 IEEE International Geoscience and Remote Sensing Symposium (IGARSS), 2016)
Embargo of 24 months from date of publishing on accepted manuscript version. Link to publisher's version: Geoscience and Remote Sensing Symposium (IGARSS), 2016 IEEE International Copyright notice: “© © 20xx IEEE policy" In this paper, a 2-dimensional scattering model for sea ice based on the Finite Element Method (FEM) is presented. The scattering problem is formulated following a physics-separate strategy. The wave in the air domain is expressed by the scattered field formulation, while the wave in the sea ice domain is expressed by the total field formulation. The two separate physics and formulations are coupled through the boundary conditions at the air-sea ice interface. The proposed FEM is tested for simulating the radar cross section (RCS) of homogeneous sea ice at C and L bands. By comparing the results of the FEM with the Small Perturbation Method (SPM), good agreements are achieved